1985
DOI: 10.1002/bjs.1800721007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bile, infection and pressure on pancreatic duct integrity

Abstract: Ionic flux, potential difference and mucosal ultrastructure have been studied in the rat bile-pancreatic duct and the effects of pressure, bile and infection on the duct evaluated. The duct remained stable after perfusion with control solution under low pressure and high pressure produced widening of intercellular spaces only. Perfusion with a bacterial solution of Escherichia coli did not effect significant changes. Sterile human bile disturbed the integrity of the duct by increasing ionic flux, altering pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
5

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
1
21
0
5
Order By: Relevance
“…Experimental studies on animals showed that presence of bacteria in bile caused the development of AP, unlike the aseptic bile (11,20,24,51). Other studies emphasized the role of increased pressure in pancreatic ducts, which next to bile infection would have a signifi cant share in evoking infl ammatory process within the pancreatic gland (11,20). Obtained own results in group of patients with SAP (73% of infected bile in CBD and 80% in gall-bladder) are higher than those in control group (respectively 62% and 52%), although this difference is of no statistical signifi cance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies on animals showed that presence of bacteria in bile caused the development of AP, unlike the aseptic bile (11,20,24,51). Other studies emphasized the role of increased pressure in pancreatic ducts, which next to bile infection would have a signifi cant share in evoking infl ammatory process within the pancreatic gland (11,20). Obtained own results in group of patients with SAP (73% of infected bile in CBD and 80% in gall-bladder) are higher than those in control group (respectively 62% and 52%), although this difference is of no statistical signifi cance.…”
Section: Discussionmentioning
confidence: 99%
“…In case of coexisting cholelithiasis, bacteria colonizing gall-bladder and bile ducts are the fi rst element. Bile acids are the second potential factor, as their damaging infl uence on epithelium of bile ducts and pancreatic ducts, as well as pancreatic follicular cells was confi rmed by experimental works (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, researchers extensively investigated the effect of BAs on the morphology and permeability of the main pancreatic duct. In these in vivo studies various BAs were perfused through the cannulated main duct and the permeability of the pancreatic duct mucosal barrier was measured using different techniques (5,15,(37)(38)(39). It has been shown that BAs in high concentrations (2-15 mM), made the ducts permeable to molecules as large as 20,000-daltons, whereas they are normally impermeable to molecules over 3,000-daltons (5,15).…”
Section: Effect Of Bile Acids On the Main Pancreatic Ductmentioning
confidence: 99%
“…It was also highlighted that infected bile is more harmful to the duct cells than sterile bile (5,37,38). The higher toxicity of infected bile is probably due to bacterial deconjugation, which produces more toxic unconjugated BAs.…”
Section: Effect Of Bile Acids On the Main Pancreatic Ductmentioning
confidence: 99%